A 'Wholly Unjustifiable Treatment of British Subject'? The Detention of W. T. Goode in the Baltic, 1919. - Storer, Colin (History, 2026)
In the summer of 1919, W. T. Goode, the Manchester Guardian's special correspondent in Russia and the Baltic, was arrested in the Estonian capital Tallinn and briefly detained aboard a British warship. Goode's detention caused a furore, leading to accusations of kidnap, heated commentary in the press and questions in parliament. Reaction to the case divided along ideological lines, with right‐wing newspapers and some officials convinced that he was a 'dangerous' Bolshevik agent, while those on the left believed that he had been illegally detained to stop him reporting the truth about conditions in Russia. This article draws on archival material and published sources to provide the first thorough analysis of the case and establish who ordered Goode's detention and why. In so doing, it argues that the case illustrates the anxieties felt in Britain in the immediate aftermath of the First World War concerning the spread of communism on the one hand, and the suppression of news from Russia on the other. At the same time, it highlights Goode's role as one of the first sympathetic British visitors to the Soviet Union and the extent to which his opponents were justified in considering him a propagandist for the Bolsheviks.